Notes of a Charter by Charles I. to James, Lord Carnegy, 1641: Constituting him keeper of the Abbey of Aberbrothock; and of an order by Mr John Garden, Factor on the Panmure Estates (1746), calling the tenantry of Edzell and Navar to be armed and ready to repel a Highland Raid (Proceedings of the Society of Antiquaries of Scotland, 1876)
John Stuart describes two historical documents that were sent to him by David Dakers Black, a Fellow from Brechin. He discusses the historical context of the documents and then provides transcriptions of them.